Case Report: Posterior Reversible Leukoencephalopathy Syndrome (PRES) as a Biologically Predictable Neurological Association in Severe COVID-19. First Reported Case From Australia and Review of Internationally Published Cases - Wijeratne, Tissa; Wijeratne, Chanith; Karimi, Leila; Sales, Carmela; Crewther, Sheila Gillard (Frontiers in Neurology, 2021)
Reports of different types of neurological manifestations of COVID-19 are rapidly increasing, including changes of posterior reversible leukoencephalopathy syndrome (PRES). Here we describe the first reported case of COVID-19 and PRES in Australia diagnosed on basis of MRI brain imaging and confirmed clinically by presence of confusion, delirium, headaches, also associated with hypertension and blood pressure variability and stable long-term kidney problems. He made full recovery as his blood pressure was controlled and clinical status was supported with appropriate rehydration. Although traditionally a rare condition, PRES is likely to be more common among patients with COVID-19 pathobiology (Involvement of Rennin-Angiotensin-Aldosterone system , downregulated ACE2 receptors, endotheliitis, cytokine storm and hyperimmune response) We advocate clinical suspicion among vulnerable patients and early brain imaging with MRI brain specifically looking for classic PRES changes and timely correction of blood pressure and supportive therapy where rehydration and blood pressure correction was the main intervention in the reported case here.